A Systematic Review of the Use of Technology in Educational Assessment Practices: Lesson Learned and Direction for Future Studies - Retnawati, Heri; Kardanova, Elena; Sumaryanto, Sumaryanto; Prasojo, Lantip Diat; Jailani, Jailani; Arliani, Elly; Hidayati, Kana; Susanti, Mathilda; Lestari, Himmawati Puji; Apino, Ezi; Rafi, Ibnu; Rosyada, Munaya Nikma; Tuanaya, Rugaya; Dewanti, Septinda Rima; Sotlikova, Rimajon; Kassymova, Gulzhaina Kuralbayevna (International Journal of Robotics and Control Systems, 2024)
Previous studies have demonstrated that technology helps achieve learning outcomes. However, many studies focus on just one aspect of technology’s role in educational assessment practices, leaving a gap in studies that examine how various aspects affect the use of technology in assessments. Hence, through a systematic work, we analyzed the extent and manner in which technology is integrated into educational assessments and how education level, domain of learning, and region may affect the use of technology. We reviewed empirical studies from two major databases (i.e., Scopus and ERIC) and a national journal whose focus and scope are on educational measurement and assessment, following PRISMA guidelines for systematic reviews. The findings of the present study are directed towards emphasizing the roles of technology in educational assessment practices and how these roles are adapted to varying educational contexts such as the level of education, the three domains of learning (i.e., cognitive, psychomotor, and affective), and the setting in which the assessment was conducted. These findings not only highlight the current roles of technology in educational assessment but also provide a roadmap for future research aimed at optimizing the integration of technology across diverse educational contexts.